IMPLEMENTASI KOMPETENSI PROFESIONAL GURU BIOLOGI DI SMA NEGERI 6 HALMAHERA UTARA - Purnomo, Eko; Syahri, Mohammad (Jurnal Kebijakan dan Pengembangan Pendidikan, 2017)
Abstract: This study aims to describe (1) the implementation of the professional competence of Biology Teachers at SMA Negeri 6 Halmahera Utara? 2) Constraints faced by teachers in the Implementation of Professional Competence of Biology Teachers in SMA 6 Halmahera Utara. This research uses the descriptive qualitative method. The subjects of this study were teachers, principals, and students. Data collection techniques used were observation, interviews, and documentation. Data were analyzed using steps of data reduction, data display, and concluding. Data validity checking techniques using source triangulation. The results of this study indicate that 1) the teacher in implementing professional competence is demonstrated by mastering the teaching process in the classroom as evidenced by the assessment of the principal who reaches 90%, learning tools and students understand biological material. The teacher also develops creative learning by using methods, models and creative learning media. Teachers take self-reflection actions through student learning outcomes that have not yet reached the KKM standard in schools. The teacher uses technology in teaching techniques through videos of teaching materials and power points, the teacher's self-development in the use of technology is supported by school facilities such as projectors, laptops, and wifi. (2) Constraints faced in the process of implementing Biology teacher Professional competence are the influence of internal and external factors, internal factors consist of student motivation and external consist of student learning environment that is the school environment in adjusting the teaching methods of teachers, family and community environment.Keywords: Biology, Teachers, Professional Competence Abstrak: Penelitian ini bertujuan untuk mendeskripsikan (1) implementasi kompetensi profesional Guru Biologi di SMA Negeri 6 Halmahera Utara? 2) Kendala yang dihadapi guru dalam Implementasi Kompetensi Profesional Guru Biologi di SMA Negeri 6 Halmahera Utara. Penelitian ini menggunakan metode kualitatif deskriptif. Subjek penelitian ini adalah guru, kepala sekolah, dan siswa. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan dokumentasi. Data dianalisis dengan menggunakan langkah-langkah reduksi data, display data, dan penarikan kesimpulan. Teknik pemeriksaan keabsahan data dengan menggunakan triangulasi sumber. Hasil penelitian ini menunjukkan bahwa 1) guru dalam mengimplementasikan kompetensi profesional ditunjukkan dengan menguasai proses mengajar di kelas dibuktikan dengan penilaian kepala sekolah yang mencapai 90%, perangkat pembelajaran dan siswa memahami materi biologi. Guru juga mengembangkan pembelajaran kreatif dengan menggunakan metode, model, dan media pembelajaran kreatif. Guru melakukan tindakan refleksi diri melalui hasil belajar siswa yang belum mencapai standar KKM di sekolah. Guru menggunakan teknologi dalam teknik mengajar melalui vidio materi ajar dan power point, pengembangan diri guru dalam pemanfaatan teknologi didukung dengan fasilitas sekolah berupa proyektor, laptop dan wifi. (2) Kendala yang dihadapi dalam proses implementasi kompetensi Profesional guru biologi adanya pengaruh faktor internal dan eksternal, faktor internal terdiri dari motivasi siswa dan ekternal terdiri dari lingkungan belajar siswa yaitu lingkungan sekolah pada penyesuaian metode mengajar guru, lingkungan keluarga dan masyarakat.Kata kunci: Biologi, Guru, Kompetensi Profesional